Recreation specialization and leisure satisfaction among long-distance running: an examination of the mediating role of place dependence and place identity - Huo, Xing; Tian, Haibo; Wang, Zhipeng; Xu, Jiao; Tang, Zhifeng (Frontiers in Psychology, 2025)
IntroductionResearchers extensively employed recreation specialization as a dependent variable or classification tool for investigating the relationship between leisure activities and sociological variables. This study challenged the conventional understanding by suggesting recreation specialization was more likely to be positively associated with leisure satisfaction through place dependence and place identity.MethodsA total of 570 questionnaire responses were collected from participants engaged in long-distance running at West Lake. JASP 0.18.3.0 software was used to examine all hypotheses in the conceptual model.ResultsThe findings provided support for the following: (1) Recreation specialization directly and positively influenced place dependence, place identity, and life satisfaction; (2) Place dependence was positively related to place identity, while both place dependence and place identity were positively associated with individuals’ life satisfaction; (3) Place dependence and place identity mediated the impact of recreation specialization on life satisfaction, with place dependence partially explaining this mediation effect through place identity.DiscussionThese findings concluded with practical and academic implications of the study. Future research should also explore the underlying mechanisms linking recreation specialization and life satisfaction.